Recent advances in aquaculture V (Blackwell Science Ltd., 1994)
This volume is a structured collection of specialist research reports which together present an international perspective on the developing field of aquaculture. As in previous volumes in the series, contributions examine the most recent advances and developments in both the scientific and production-based areas of the industry but a particular feature of Volume V is the greater emphasis on some of the wider issues including water resources and socio-economic concerns. This reflects a growing awareness amongst planners, development agencies and industry leaders that aquaculture needs to be reviewed in its broadest context to ensure that development along productive and sustainable paths is not achieved at the cost of social dislocation and environmental damage.